Sodium Intake and Stress as Risk Factors for Hypertension among Outpatients at Talang Jawa Health Center - Mentari Nurhidayah; Asep Jalaludin; Dewi Woro Astuti (Jurnal Kesehatan Cendikia Jenius, 2025)
Hypertension is a global health problem with an increasing prevalence, including in South Lampung Regency. One of its main causes is modifiable risk factors such as excessive sodium intake and psychological stress. This study aimed to determine the relationship between sodium intake and stress levels with the incidence of hypertension in the outpatient unit of UPTD Talang Jawa Health Center. This research employed a cross-sectional design with a total sample of 37 respondents aged 18–65 years, selected using a consecutive sampling technique. Data collection was conducted from May to June 2025 using a Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), the Perceived Stress Scale (PSS-10), and blood pressure measurements with a sphygmomanometer. Data were analyzed using the chi-square test with a significance level of 5%. The results showed that the prevalence of hypertension was 73%, with 40.5% of respondents having high sodium intake and 48.6% experiencing severe stress. A significant relationship was found between sodium intake and hypertension (p = 0.002), as well as between stress levels and hypertension (p = 0.001). In conclusion, high sodium intake and severe stress are significantly associated with hypertension. It is recommended that health centers strengthen nutrition education and stress management to prevent hypertension.